Safety evaluation of dried L-tryptophan fermentation product in Sprague-Dawley rats. (2022) - Ko, Soo Min; Park, Ji-Eun; Kim, Sang-Ho; Park, Myeong Kyu; Seol, Ja Kyung; Heo, In Kyung; Shin, Yong-Uk; Kim, So-Young; Kim, Yang Hee; Son, Woo-Chan
Abstract: The subchronic toxicity of oral L -tryptophan produced by fermentation with metabolically engineered Corynebacterium glutamicum was evaluated in Sprague-Dawley rats. Doses of 0, 500, 1000, and 2000 mg/kg/day were administered to groups of 10 male and 10 female rats for 90 days. For the groups administered 0 and 2000 mg/kg/day, an additional 5 male and 5 female rats were tested as a recovery group. No adverse effects associated with the test substance were observed in all rats during the 90-day administration of the product, irrespective of dose, and at 4 weeks of recovery at dosages of 0 and 2000 mg/kg/day. Furthermore, histochemical and immunohistochemical analyses for L -tryptophan-associated eosinophilia-myalgia syndrome (EMS) did not reveal significant changes in both sexes of groups administered 0 or 2000 mg/kg/day. Based on these results, it could be concluded that there were no significant adverse effects related to the test substance in all animals; therefore, dried L -tryptophan fermentation product can be used as feed additive material. Highlights: L -tryptophan has long been used as a feed additive in livestock. Subchronic toxicity of L -tryptophan (0–2000 mg/kg/day) was evaluated in SD rats. L -tryptophan did not induce significant changes in all parameters. Consumption of L -tryptophan would not have significant safety concerns in humans.